THE PHARMACOKINETICS OF 2 DOSES (50 ÂµG AND 100 ÂµG) LEVOTHYROXINE TREATMENT IN ATHYREOTIC PATIENTS - Tewthanom, Karunrat; Jongjaroenprasert, Walaya (International Journal of Applied Pharmaceutics, 2016)
Objective: Hypothyroid has still be a problem in Thailand. Lack of pharmacokinetics information of levothyroxine in athyreotic patients for modify dosing. Therefore, the aim of this study was to investigate the pharmacokinetic parameters of 2 doses of levothyroxine(50 mg and 100 mg) in such group of patients. Methods: The 24 athyreotic patients were recruited and randomly assigned to receive 50 mg or 100 mg of levothyroxine. The pharmacokinetic parameters (Cmax, Tmax, AUC0-8, ke, T1/2 and Vd) of FT4 and TSH were calculated by the non-compartment model. The parameters of 2 doses were compared. Results: From the results found that, by monitoring FT4, there was no statistically significant difference (p>0.05) of almost all pharmacokinetic parameters between 2 doses except Cmax which has significant greater in 100 mg of levothyroxine. While all pharmacokinetics parameters of TSH were not statistically significant difference. The use of non-compartment model seems appropriate for calculation of pharmacokinetic parameters of FT4 (R2 = 0.81) while it has poor predictive capacity in terms of TSH (R2 = 0.24). Conclusion: In conclusion, administration of 50 mg and 100 mg of levothyroxine to athyreotic patients have similar pharmacokinetic in term of FT4(non-significant different in Tmax, AUC) and TSH. Further study of these parameters in more subjects is needed.